Pemanfaatan Dana Desa Dalam Pemberdayaan Masyarakat Pada Desa Kopeng, Kecamatan Getasan, Kabupaten Semarang - Christian Kenny Alexander Wuisan; Aprina Nugrahesthy Sulistya Hapsari (Jurnal Akuntansi dan Perpajakan, 2020)
This study is intended to determine the use or utilization of village funds in Kopeng Village, especially in the field of community empowerment. The purpose of this study is to explain the allocation of village funds used for community empowerment in Kopeng Village, because according to government regulations the purpose of disbursing village funds is to help improve the village economy by empowering the community and not solely for village operational activities. Data collection methods in this study use descriptive qualitative methods. The data used in this study are primary data obtained from interviews and supported by evidence through documentation. Interviews were conducted with resource persons related to the research topic, namely village officials. Furthermore, the data collected will be analyzed into several stages, namely data reduction, triangulation, data presentation, and drawing conclusions. The results of research conducted in Kopeng Village show that the utilization of village funds for empowerment and community development is still not optimal because it is still focused on the field of development, especially infrastructure. DOI: 10.26905/ap.v6i1.4034